Association of concomitant autoimmunity with the disease features and long-term treatment and health outcomes in Celiac disease - Tauschi, Riku; Eurén, Anna; Vuorela, Nina; Koskimaa, Sara; Huhtala, Heini; Kaukinen, Katri; Kivelä, Laura; Kurppa, Kalle (Frontiers in Medicine, 2022)
Background: Celiac disease (CeD) is often accompanied by other autoimmune diseases (AID). However, the association of co-existing autoimmunity with the presentation and treatment success in CeD is unclear. We investigated these issues with a large and well-defined cohort of Finnish patients. Methods: Adult CeD patients (n=806) were collected from multiple heath care sites via nationwide recruitment. They were interviewed, underwent measurement of CeD autoantibodies, and filled out questionnaires to ascertain quality of life (PGWB) and gastrointestinal symptoms (GSRS) after a median of 9.7 years on a gluten-free diet. Data were supplemented retrospectively from patient records. The results were compared between CeD patients with and without a coexisting AID. Results: Altogether 185 patients had CeD+AID and 621 had CeD only. At CeD diagnosis, patients with CeD+AID were older (median 42 vs. 36 years, p=0.010) and had more joint symptoms (9.1% vs. 4.2%, p=0.011), whereas the groups were comparable in sex, family history of CeD, other presenting symptoms, proportion of screen-detected subjects, and severity of duodenal lesion. During follow-up on gluten-free diet, CeD+AID patients experienced poorer general health (median score 12 vs. 14, p<0.001) in PGWB, more overall gastrointestinal symptoms (2.1 vs. 1.9, p=0.001), and constipation (2.0 vs 1.7, p<0.001) in GSRS, whereas there was no difference in histological and serological recovery, dietary adherence, use of gluten-free oats, smoking, and presence of regular follow-up. Conclusions: Co-existing AID was not significantly associated with the baseline features or with most long-term outcomes in CeD. However, the increased prevalence of gastrointestinal symptoms and reduced poorer self-perceived health during treatment indicates these patients’ need for special support.